1999
DOI: 10.1021/jp992270d
|View full text |Cite
|
Sign up to set email alerts
|

First Demonstration of in Situ Electrochemical Control of a Base Metal Catalyst:  Spectroscopic and Kinetic Study of the CO + NO Reaction over Na-Promoted Cu

Abstract: Controlled, reversible electrochemical promotion (EP) of a base metal catalyst has been demonstrated for the first time. Electropumping of Na from a ′′ alumina solid electrolyte to a Cu film catalyst results in large improvements in both activity and selectivity of the latter. In the catalytic reduction of NO by CO, the reactive behavior, surface composition, and response to EP are a strong function of the composition of the reactant gas. Electron spectroscopic data show that these effects are due to pumping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…Previous XPS studies involving in situ transfer of promoted and poisoned ex-reactor electrochemically promoted catalysts to the spectrometer analysis chamber showed [23] that in the case of NO+C 3 H 6 the Na-containing promoting (or poisoning) phase consists principally of a mixture of NaNO 2 , NaNO 3 and NaCO 3 . Most recently, Lambert and co-workers [28,40] attributed the rate inhibition primarily to the formation of thick (three-dimensional) films of alkali carbonate that cover the surface and are stable at elevated reaction temperatures. They shown that such alkali carbonates are easily formed in the present of carbon-rich molecules, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous XPS studies involving in situ transfer of promoted and poisoned ex-reactor electrochemically promoted catalysts to the spectrometer analysis chamber showed [23] that in the case of NO+C 3 H 6 the Na-containing promoting (or poisoning) phase consists principally of a mixture of NaNO 2 , NaNO 3 and NaCO 3 . Most recently, Lambert and co-workers [28,40] attributed the rate inhibition primarily to the formation of thick (three-dimensional) films of alkali carbonate that cover the surface and are stable at elevated reaction temperatures. They shown that such alkali carbonates are easily formed in the present of carbon-rich molecules, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…propene [40]. On the other hand they showed [28] that when the promoter phase consists exclusively of alkali nitrates, submonolayer films of this component would be expected to be stable [41] at used reaction temperatures. In contrary, thick films of alkali nitrates cannot be built up at the used reaction temperatures because of their volatility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the progress made in the development and understanding of the phenomenon of electrochemical promotion over the years could not be conceived without the in situ spectroscopy studies performed by the group of professor Lambert and co-workers [34][35][36][37][38][39][40][41][42][43][44][45]. In all cases, the spectra were obtained immediately after exposing the appropriately polarized catalyst film (either unpromoted or electrochemically promoted) to conditions of temperature and reactant partial pressures similar to those encountered in the electrochemical promotion reactor, in order to simulate the different surface conditions of interest.…”
Section: In Situ Characterization Of Alkali-promoted Catalyst Surfacesmentioning
confidence: 99%